Conserved Peptide with Therapeutic Potential to Overcome Nasopharyngeal Carcinoma - R, Muhaimin; S, Widyarti; N, Widodo (IIUM Medical Journal Malaysia, 2014)
Nasopharyngeal carcinoma (NPC) is a squamous-cell carcinoma that arises in the upper lining epithelium of the nasopharynx. In this study, conserved peptide (Ulin-1) of Epstein-Barr virus constructed by Biomodelling and Biocomputation was tested for its ability to stimulate B cells to produce specific antibodies. Spleen cells were isolated and cultured with anti-CD3 and lipopolysaccharide (LPS), and treated or not treated with Ulin-1. Cell culture was harvested six days after incubation and analyzed by flow cytometry. Here, we demonstrated the ability of Ulin-1 to stimulate B cells to produce specific antibodies. The results of this study illustrate the importance of Ulin-1 engineered by Biomodelling and Biocomputation as both active and passive immunization agents against nasopharyngeal cancer.